2009
DOI: 10.1002/ejoc.200801024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β‐(1→2)‐Linked Oligomannosides

Abstract: β‐(1→2)‐Linked oligomannosides constitute an important class of carbohydrate structures located on the cell surface of several Candida species, including C. albicans. As a result of the immunostimulating properties of such compounds, the upscaling of their synthesis is relevant. In this paper, a highly stereoselective synthesis of β‐(1→2)‐linked oligomannosides was performed by further development of and modifications to the methodologies described earlier in the literature. In addition to the synthesis of ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…The highest yield (64 %) was achieved starting from α‐bromide 4 using indium(III) chloride as activator; under the same conditions the α‐iodide 2 gave a yield of 22 %. Direct glycosylation of the peracetylated d ‐glucose 3 under BF 3 ⋅ OEt 2 activation gave a yield of 4.8 %, which revealed that glucose derivatives, in comparison with the corresponding mannosides, are not suitable for such transformations …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest yield (64 %) was achieved starting from α‐bromide 4 using indium(III) chloride as activator; under the same conditions the α‐iodide 2 gave a yield of 22 %. Direct glycosylation of the peracetylated d ‐glucose 3 under BF 3 ⋅ OEt 2 activation gave a yield of 4.8 %, which revealed that glucose derivatives, in comparison with the corresponding mannosides, are not suitable for such transformations …”
Section: Resultsmentioning
confidence: 99%
“…Direct glycosylation of the peracetylated d-glucose 3 under BF 3 ·OEt 2 activation gave ay ield of 4.8 %, which revealed that glucose derivatives, in comparison with the corresponding mannosides, are not suitable for such transformations. [18] Thioethers are very convenient compounds for glycosylation strategies, because at hioether group connected to an anomeric center can serve both as at emporary protecting group and as an activatable group for glycosylation reactions. Thus, we synthesized the two b-thioethers 6 and 7 under different conditions.…”
Section: Donor Building Block Synthesesmentioning
confidence: 99%
“…1A, 2A, 3A, and 4A), were prepared by applying and further modifying the recently developed methodologies for construction of ␤-(1¡2)-mannosidic linkages by Crich and others (7). The synthesis procedures have been published previously by us (9,10,28). The compounds prepared were designed as simple mimics and analogues of the hydrolyzed oligosaccharide fractions from the C. albicans cell wall, with the ␤-(1¡2) linkage serving as a basis for all structural modifications.…”
mentioning
confidence: 99%
“…Since disaccharides 3α , 3β , 18 ,9c 19 ,9a 21 , and 22 are potential glycosyl donors, it is necessary to confirm their structures for future applications. Thus, all these disaccharides were rigorously characterized by NMR spectroscopy and selected characteristic data are depicted in Table 4.…”
Section: Resultsmentioning
confidence: 99%